Innovation as an Accelerator of Competitiveness and Economic Development - Valentinavičius, Stasys (Ekonomika, 2005)
The article explores the importance and strategic objectives of innovation as an accelerator of competitiveness and economic development. It presents an analysis of innovation performance in Lithuania and other European Union (EU) economies. The possible trends and methods of innovation development are discussed.Objectives: a comparative analysis of innovation performance in Lithuania and suggestions for its development.Study focus: current innovation performance in Lithuania and means of its development.Methods: analysis and review of scientific material, publications and statistical data.The innovation performance study is based on data provided by Lithuanian Department of Statistics, supported by reports of European Commission, World Bank as well as other institutions, findings of numerous researchers, reviews and legal acts of Lithuania.